STUDI JENIS BURUNG YANG DIPERDAGANGKAN DI KOTA KETAPANG - Juhardiansyah, .; Erianto, .; Idham, M (JURNAL HUTAN LESTARI, 2019)
This study aims to explore information on the types of birds that are traded, to know the description of the location of birds originating, to know the status of protected species traded, to know the locations of shelters and the sale of traded birds, to know the number and prices of birds traded. This research was conducted in Ketapang City for 10 days effectively in the field, with the research method in field data collection using snowball sampling technique, namely determining key respondents to then determine other respondents who also knew the relevant information from previous respondents. The results of the data obtained at the time of the study were 267 individuals from 31 species of birds traded. The origin of the traded birds is a specific natural catch in the Jelai Hulu sub-district, Tumbang Titi sub-district, Kendawangan sub-district, Sandai sub-district, Laur sub-district, Matan Hilir Selatan sub-district, Matan Hilir Utara sub-district, Muara Pawan sub-district, and Teluk Batang sub-district and Kayong Utara regency. There are 11 protected bird species as a whole belonging to 15 tribes (families). Of these types, they fall into the protected category according to the Indonesian Law. Birds are in the category of Apendix II CITES and birds are listed in the IUCN Red List category. As for the research on the trading location there were 10 respondents 2 people in the hunter category and 8 bird shops / traders. while the most types of birds sold per type are Kacer (copshycus saularis) as many as 50 Tails / Individual, Murai batu (Copsychus malabaricus) and Serindit (Loriculus galgulus) as many as 44 Tails / Individuals.Keyword: Bird Species, Bird Trade, Ketapang